Evidence of non‐site‐specific agricultural management effects on the score of visual soil quality indicators - Teixeira, Fernando; Lemann, Tatenda; Ferreira, Carla; Glavan, Matjaž; Zoltán, Tóth; Hermann, Tamás; Lipiec, Jerzy; Frąc, Magdalena; Reintam, Endla; Xu, Minggang; Fan, Hongzhu; Ritsema, Coen (Soil use and management, 2023)
This study investigates 11 agricultural management practices (AMPs) and their effects on seven visual soil quality indicators and soil aggregate stability. The survey carried out across eight pedoclimatic zones in Europe and China was based on visual soil assessments (New Zealand VSA method) performed on soils subject to different soil management practices and nearby similar soils, under similar farming features, without the distinctive soil management practice (control). Fisher's exact test was used to test if the management treatment was independent of the score of each visual soil quality indicator and to test if the management treatment produced a higher frequency of the score ‘good’. The results showed a statistically significant (α < .05) higher frequency of the score ‘good’ for ‘soil structure and consistency’ and/or ‘soil porosity’ for six AMPs. For no‐till AMP, the null hypothesis can also be rejected for ‘susceptibility to erosion’ and ‘soil stability’ and for ‘mulching + permanent soil cover’ AMP, for the ‘presence of tillage pan’ and ‘soil colour’. The hypothesis that the management treatment was independent of the score of each indicator was rejected for ‘soil structure and consistency’ of three AMPs, for ‘soil porosity’ of three AMPs, for ‘soil colour’ of one AMP and for the ‘presence of tillage pan’ of one AMP. This study demonstrates that farming systems sharing a common influential soil management practice at different locations and with different soil types significantly affect the score of some visual soil quality indicators.